2015
DOI: 10.1080/14445921.2015.1026199
|View full text |Cite
|
Sign up to set email alerts
|

Does the farmer want a market? Factors impacting on participation by local producers in farmers markets

Abstract: This paper presents the findings of a study which aimed to investigate the barriers to participation in farmers' markets by the wider farming community in South Australia (SA) with a particular focus on small-to-medium-sized primary producers. While the experiences and motivations of farmers participating in markets outside Australia have been studied, there has been very little research conducted in Australia or internationally on raw food producers who remain outside the farmers' market community. Both descr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
2

Year Published

2016
2016
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(8 citation statements)
references
References 5 publications
0
6
2
Order By: Relevance
“…Brown's (2002) findings support the proposition that larger producers tend to see the economics of FMs as adverse. On the other hand, her findings contradict Kupke and Page's (2015) proposition regarding part-time producers' participation in FMs. Her findings suggest that many FMs' producers are part-time producers with additional occupations and household incomes (Brown, 2002).…”
Section: Farmers' Markets As a Real-life Manifestation Of Sfscs: Chalcontrasting
confidence: 85%
See 1 more Smart Citation
“…Brown's (2002) findings support the proposition that larger producers tend to see the economics of FMs as adverse. On the other hand, her findings contradict Kupke and Page's (2015) proposition regarding part-time producers' participation in FMs. Her findings suggest that many FMs' producers are part-time producers with additional occupations and household incomes (Brown, 2002).…”
Section: Farmers' Markets As a Real-life Manifestation Of Sfscs: Chalcontrasting
confidence: 85%
“…On the other hand, the desire to establish social connections, with consumers and other producers, and protecting the environment are also recognised by some producers (Migliore et al, 2015). Kupke and Page (2015) suggest that producers' attitudes towards engaging in FMs reflect their personal circumstances. They further propose that larger and part-time producers are less motivated to engage in FMs.…”
Section: Farmers' Markets As a Real-life Manifestation Of Sfscs: Chalmentioning
confidence: 99%
“…In Turkey, in areas not suitable for industrial development but open to improvement of their agricultural economy, increasing the production of local foods is a good opportunity for the local economy. It has been shown that production of local products by small businesses without the need for extensive technology is extremely effective in protecting rural areas, promoting sustainable agriculture, and responding to consumers' growing interest in healthy natural food products (Kupke & Page, 2015;Zhao et al 2015).…”
Section: Introductionmentioning
confidence: 99%
“…However, farmers also face barriers moving in this direction (Mount, 2012). In Southern Australia, Kupke and Page (2015) concluded that farmers are "time poor and spending precious weekends behind a stall does not hold much attraction" (p. 73). Kupke and Page (2015) also comment on the lack of management and staff, and issues around transport and transport costs associated with accessing the market.…”
Section: Introductionmentioning
confidence: 99%
“…In Southern Australia, Kupke and Page (2015) concluded that farmers are "time poor and spending precious weekends behind a stall does not hold much attraction" (p. 73). Kupke and Page (2015) also comment on the lack of management and staff, and issues around transport and transport costs associated with accessing the market. Moving forward, Guptill and Wilkins (2002) and Abatekassa and Peterson (2011) suggest that more attention needs to be focused at the retail end of the conventional food supply chain.…”
Section: Introductionmentioning
confidence: 99%